2018
DOI: 10.1007/s00420-018-1334-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners

Abstract: The well-established association of the genomic region 15q25 to lung cancer might be influenced by exposure to radon among uranium miners. Furthermore, lung cancer susceptibility is related to the functional capability of DNA damage signaling via ubiquitination processes and repair of radiation-induced double-strand breaks by the single-strand annealing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 56 publications
(89 reference statements)
0
26
0
2
Order By: Relevance
“…E.g. GxE interaction effects for LC have been observed smoking [48], exposure to asbestos bres [49,50] and exposure to radon [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…E.g. GxE interaction effects for LC have been observed smoking [48], exposure to asbestos bres [49,50] and exposure to radon [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…An overview of the main cytogenetic and "omics" biomonitoring studies focused on the effect of radon on various biomarkers including microRNAs is reported in Figure 5 and Table 1. Micronuclei in blood lymphocytes Uranium-exposed subjects had higher micronuclei frequency than non-exposed Rosenberger et al, 2019 [53] In vivo Infinium OncoArray-500K 15,077 cases (lung cancer) and 13,522 controls, including 463 former uranium miners (61 cases:402 controls) 49 of 15 077 (0.3%) LC cases and 259 of 13 522 cancer-free controls (1.9%) had been occupationally exposed by a high cumulative dose exposure to radon and its progeny (WLM > 50) occupational radon exposure was categorized into ≤50 ("unexposed") and >50 WLM ("exposed") as a threshold for significant elevated relative lung cancer risk Genes belonging to the Gene Ontology term "DNA dealkylation involved in DNA repair" (GO:0006307; p = 0.0139) or the gene family HGNC:476 "microRNAs" (p = 0.0159) were enriched with LD-blockwise significance Estimates of potential radon exposure were based on long-term radon measurements from 479,000 homes across Great Britain and provided with a spatial resolution of 75-metre buffers as the percentage of dwellings exceeding the 200 Bq/m 3 . Radon Action Level in 6 classes: 1 (0-1%), 2…”
Section: Epigenetic Factors In the Development Of Radon-induced Lung mentioning
confidence: 99%
“…Examining the mutational landscape in 439 non-smoker lung cancers a higher frequency in high (i.e., >45 Bq/m 3 ) vs. low exposed Radon patients was found for mutations targeting the DNA damage response/repair machinery (ATR, ATRX, BARD1, RAD50, and SMARCA4), histonedeacetylase2 (HDAC2), and inhibitor of nuclear factor kappaB kinase subunit epsilon (IKBKE), as well as EGFRand TP53 [52]. It was shown that radon-induced lung cancer susceptibility is related to genes involving to DNA dealkylation [53]. Radon exposure was found to be associated with exon 19 EGFR and ALK mutations in 393 never-smokers lung cancer cases [54] as well as increased TP53 mutations comparing 83 non-smokers vs. 250 smoking lung cancers [55].…”
Section: Radon Exposure and Lung Cancer: Pathogenic Mechanisms (Genotmentioning
confidence: 99%
“…The radiation-associated breast cancer risk also varied significantly by linked markers in chromosome 5p12 in the mitochondrial ribosomal protein S30 (MRPS30) gene (Bhatti et al 2010). A recent study in uranium miners suggests an interaction between radon exposure and the genomic region 15q25 on lung cancer risk (Rosenberger et al 2018).…”
Section: Factors That May Play a Role In Radiation Sensitivity And Sumentioning
confidence: 99%